Epidemiology of Risk Factors for Post-Covid-19 Associated Digestive Diseases by Occupational Type and Ethnic Group - Boltaboev A. M.; Mamasaliev N. S.; Mamasaliev Z. N.; Umurzaqov O.T.; Qurbonova R. R.; Boltaboeva D. I. (Scientific Trends, 2025)
The fact that the flow of studies and publications devoted to the Covid-19 pandemic has increased and continues to increase worldwide is evident from the literature review or the reader-researcher may conclude that this is an indication that there are still “mysteries” in the Covid-19 infection. Among these problems, the issue of studying the epidemiology, prevention and radical improvement of treatment methods for Post-Covid-19-associated digestive system diseases is also a cross-cutting and acute medical and social problem. Preventive gastroenterology has begun to develop and find its place in modern medicine, for example, in the case of the Post-Covid-19 population, and the scope of scientific and priority views on reasonable guidelines and recommendations for its improvement has increased. They should be taken into account when determining the topics and directions of scientific research. In our opinion, a very scientific and practical conclusion is drawn: the level of study of modern epidemiological, clinical, pharmacotherapeutic and prophylactic aspects of post-Covid-19 associated digestive system diseases does not meet the requirements. There is a need and a need to analyze and study the existing data from the perspective of preventive medicine. There is a lack of scientific research on the development of radically improved programs for the prevention and treatment of post-Covid-19 associated digestive system diseases and their justification.
Keywords: COVID-19, Post-Covid-19, associated digestive system diseases, epidemiology, prevention, treatment.